Implementasi Risk-Based Tax Audit dan Digitalisasi Sistem Coretax dalam Meningkatkan Kepatuhan Pajak: Studi Kasus pada KPP Pratama Kebumen - Susi Astuti; Mispiyanti Mispiyanti (Politeknik Ganesha Medan, 2026)
This study analyzes the implementation of tax audits at the Kebumen Primary Tax Office (KPP Pratama Kebumen) in the context of regulatory reform through Minister of Finance Regulation (PMK) No. 15 of 2025, the adoption of a risk-based audit approach, and the digital transformation of tax administration through the Coretax system. Effective tax audits play an important role in improving taxpayer compliance, ensuring legal certainty, and strengthening accountability in tax administration. Recent regulatory reforms and the digitalization of tax administration have significantly transformed audit procedures, requiring stronger procedural readiness, competent human resources, and integrated data systems to ensure that tax audits are implemented effectively. This study employs a qualitative phenomenological approach to explore the experiences and perceptions of tax auditors in conducting tax audits following regulatory reform and the implementation of digital tax administration through Coretax. Primary data were obtained through in-depth interviews with informants who have direct experience in the tax audit process. Questionnaires were used as supporting data to capture collective perceptions of tax auditors regarding several dimensions of audit implementation, including regulatory clarity, the application of risk-based audits, auditor competence, and the use of digital technology. Data from interviews and questionnaires were integrated through methodological triangulation to strengthen the credibility of the findings. The results identify five main themes: procedural consistency and regulatory certainty, the implementation of risk-based audits, data quality as a determinant of audit effectiveness, the dynamics of fiscal corrections and tax disputes, and digital transformation alongside organizational readiness. Overall, tax audits at KPP Pratama Kebumen are aligned with the regulatory framework and are generally perceived as effective. However, the effectiveness of risk-based audit selection and audit outcomes remains highly dependent on data readiness, system integration, and the availability of reliable audit evidence.